2021
DOI: 10.1177/23800844211049406
|View full text |Cite
|
Sign up to set email alerts
|

Removable Denture Wearing as a Risk Predictor for Pneumonia Incidence and Time to Event in Older Adults

Abstract: Introduction: Older adults are more susceptible to a common respiratory infection: pneumonia. Nearly 1 million older adults per year are hospitalized for community-acquired pneumonia in the United States. Objective: To examine whether wearing removable dentures are associated with an increased risk of pneumonia incidence in a geriatric population. Methods: We conducted a retrospective cohort study among patients >65 y of age within a large academic health system (University of Rochester Medical Center). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Some studies have reported an association between removable prosthesis-wearing or poor prosthesis hygiene and community-or nosocomial-acquired pneumonia. [4][5][6] The colonization of respiratory pathogens on prostheses may increase the risk of respiratory infections through aspiration from the oropharynx into the lower respiratory tract. 2 Three included studies in the present review found high detection rates of opportunistic respiratory pathogens isolated from removable prosthesis biofilm, ranging from 46.0% to 64.6%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have reported an association between removable prosthesis-wearing or poor prosthesis hygiene and community-or nosocomial-acquired pneumonia. [4][5][6] The colonization of respiratory pathogens on prostheses may increase the risk of respiratory infections through aspiration from the oropharynx into the lower respiratory tract. 2 Three included studies in the present review found high detection rates of opportunistic respiratory pathogens isolated from removable prosthesis biofilm, ranging from 46.0% to 64.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported an association between removable prosthesis‐wearing or poor prosthesis hygiene and community‐ or nosocomial‐acquired pneumonia 4–6 . The colonization of respiratory pathogens on prostheses may increase the risk of respiratory infections through aspiration from the oropharynx into the lower respiratory tract 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, users of removable dentures, mostly elderly individuals, deserve special attention 4 , 5 since it was found that wearing these prostheses, especially during sleep, 6 is a risk predictor for the incidence of pneumonia in the geriatric population. 7 Even greater attention should be directed to hospitalized elderly people because the presence of oral and denture biofilm associated with compromised host immunity and the aspiration of the contents present in the oropharynx into the lower respiratory tract increases the risk of AP, especially 48 h after hospitalization. 8 Furthermore, the greater lack of autonomy also leads to less satisfactory cleaning of dentures during hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…While the incidence of complete edentulism is declining, many people are still completely or partially edentulous and wear prosthetic devices to replace the missing teeth. Using an 8-y retrospective longitudinal design, Alzamil et al (2021) measured the incidence and time to event of pneumonia in a population of independently living older people (65+ y) wearing and not wearing any type of removable dental prostheses ( n = ~2,300). Among other concerning findings, they report that pneumonia risk was significantly associated with use of dental prostheses and that those who wear dental prostheses have 6 times greater risk of contracting pneumonia than others who do not use dental prostheses.…”
mentioning
confidence: 99%